Consumption of Alcoholic Beverages among Adolescents in Kinshasa: Diagnosis and Therapy (Global Journal of Human-Social Science, 2023)
The study analyzed the age of onset of alcohol consumption among adolescents in Kinshasa The study led to the following results 44 2 of adolescents in the cityprovince of Kinshasa start consuming alcohol at the age of 16- 17 These teenagers use alcohol to solve a disturbing problem 33 3 The following factors promote alcohol consumption parents p 0 432 r 0 000 friends p 0 418 r 0 000 culture p 0 627 r 0 000 social classes p 0 639 r 0 000 family heredity p 0 401 r 0 000 school p 0 361 r 0 000 availability and publicity p 0 349 r 0 000 and alcohol consumption by adolescents
Keywords: consumption; drink; alcohol; teenagers; kinshasa